2021
DOI: 10.3389/fbioe.2021.736679
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Copper-Binding Peptide That Self-Assembles Into a Transparent Antibacterial and Antiviral Coating

Abstract: The health, economy, and quality of life all over the world are greatly affected by bacterial infections and viral outbreaks. Bacterial cells and viruses, such as influenza, can spread through contaminated surfaces and fomites. Therefore, a possible way to fight these pathogens is to utilize antibacterial and antiviral coatings, which reduce their numbers on contaminated surfaces. Here, we present a novel short peptide that can self-assemble, adhere to various surfaces, and bind different metal ions such as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This can be an option which deserves further in-depth studies, as reported for other antimicrobial peptides and their complexes. [42][43][44][45] More in detail, higher activity in the presence of metal ions with respect to the ligand itself (Table 5) is more evident for A7S/A8S and WT (8)(9)(10)(11)(12)(13)(14)(15). The only exceptions are against the microorganism P. mirabilis, for which neither the peptide nor the metal/peptide systems are effective, and K. ozaenae for which the presence of Zn 2+ seems to decrease the antimicrobial activity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This can be an option which deserves further in-depth studies, as reported for other antimicrobial peptides and their complexes. [42][43][44][45] More in detail, higher activity in the presence of metal ions with respect to the ligand itself (Table 5) is more evident for A7S/A8S and WT (8)(9)(10)(11)(12)(13)(14)(15). The only exceptions are against the microorganism P. mirabilis, for which neither the peptide nor the metal/peptide systems are effective, and K. ozaenae for which the presence of Zn 2+ seems to decrease the antimicrobial activity.…”
Section: Discussionmentioning
confidence: 96%
“…This can be an option which deserves further in-depth studies, as reported for other antimicrobial peptides and their complexes. 42–45…”
Section: Discussionmentioning
confidence: 99%
“…Peptides are of great promise as antimicrobial agents in agriculture due to their exceptional biocompatibility, low toxicity, and wide-ranging efficacy. Additionally, specific peptides possess the ability to efficiently bind to metal, potentially leading to a reduction in metal levels within the pesticide formulation.…”
Section: Introductionmentioning
confidence: 99%